2021
DOI: 10.3390/polysaccharides2010011
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer Matrices Based on Chitosan and Fibroin: A Review Focused on Methods for Studying Surface Properties

Abstract: For the creation of tissue-engineered structures based on natural biopolymers with the necessary chemical, physical, adhesive, morphological, and regenerative properties, biocompatible materials based on polysaccharides and proteins are used. This work is devoted to a problem of the technology of polymeric materials for biomedical purposes: the creation of biopolymer tissue engineering matrix and the development of a methodology for studying morphology and functional properties of their surface to establish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 106 publications
0
3
0
2
Order By: Relevance
“…Notably, chitosan with a high degree of deacetylation is commonly used in fibroin composites [83][84][85][86][87]. A high degree of deacetylation results in a higher number of protonated amino groups in aqueous solutions, thus enhancing solubility and biocompatibility [88]. The structure of the silk fibroin heavy chain was obtained from https://alphafold.ebi.ac.uk/entry/B0FRJ4 accessed on 6 May 2024 (fibroin heavy chain Fib-h).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, chitosan with a high degree of deacetylation is commonly used in fibroin composites [83][84][85][86][87]. A high degree of deacetylation results in a higher number of protonated amino groups in aqueous solutions, thus enhancing solubility and biocompatibility [88]. The structure of the silk fibroin heavy chain was obtained from https://alphafold.ebi.ac.uk/entry/B0FRJ4 accessed on 6 May 2024 (fibroin heavy chain Fib-h).…”
Section: Methodsmentioning
confidence: 99%
“…These composites aim to reduce the environmental impact by using renewable resources such as plant fibers (date palm, flax, banana ..) and biopolymers from sources such as corn or cellulose (Mohammed 2015, Srinivasan et al 2021. These materials provide many benefits, including the reduction of materials from non-renewable sources and a lower environmental impact (Jawad et al 2011, Zakharova and Kildeeva 2021, Djafar et al 2024. Bio-composites can be used and classified based on the use of biodegradable materials, with the reinforcement of natural fibers and biopolymer matrices being considered (Verma 2021, Maroua et al 2024.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that silk fibroin can form strong intermolecular interactions with polysaccharides. [ 32–34 ] Therefore, we hypothesized that the use of SNFs as reinforcement is a potential strategy for preparing CS fibers with enhanced mechanical properties and hierarchical structure. In this study, SNFs were extracted from natural silkworm silks by chemical pretreatment and mechanical disintegration and were utilized as reinforcing nanofiller to enhance the mechanical properties of wet‐spun CS fibers.…”
Section: Introductionmentioning
confidence: 99%